Binary nonmetal S and P-co-doping into mesoporous PtPd nanocages boosts oxygen reduction electrocatalysis. Issue 27 (7th July 2020) - Yin, Shuli; Xu, You; Liu, Songliang; Yu, Hongjie; Wang, Ziqiang; Li, Xiaonian; Wang, Liang; Wang, Hongjing
Abstract : S and P-co-doped mesoporous PtPd nanocages were synthesized and they demonstrated enhanced electrocatalytic performance for the oxygen reduction reaction. Abstract : The development of doped noble metal catalysts with nonmetal elements to improve the catalytic performance toward the oxygen reduction reaction (ORR) is significant for proton exchange membrane fuel cell technology. Here, we report a one-pot for dual-nonmetal-doping strategy for the synthesis of S and P-co-doped mesoporous PtPd nanocages (PtPdSP mNCs) by using pre-synthesized mesoporous PtPd nanocages (PtPd mNCs) as the precursor and triphenylphosphine sulphide as both S and P sources. Benefitting from the combined advantages of metal–nonmetal incorporation, hollow cavity and surface porosity, the resultant quaternary PtPdSP mNCs exhibit outstanding ORR activity and long-term stability. This research work provides a good strategy for the doping of two or more selected nonmetallic elements into metallic nanocrystals with a controllable structure and composition.